Positive effects of acute and moderate physical exercise on cognitive function - Kashihara, K.; Maruyama, T.; Murota, M.; Nakahar, Y. (Journal of Physiological Anthropology, 2009)
Some researchers have reported that moderate physical exercise improves cognitive function, and that exercise at high intensity beyond the optimal point attenuates performance, in an inverted U-relationship. The optimal intensity of physical exercise for cognitive function might be related closely to the anaerobic threshold. It has been regarded as an extremely useful index for effective training intensity in cardiorespiratory fitness. This review specifically addresses acute physical exercise around the anaerobic threshold in healthy subjects and its effects on task performance during or after exercise. We discuss physiological factors for the facilitating effect of moderate exercise on cognitive function, which indicates the initial basis in complicated mechanisms of the benefits of physical exercise on cognitive performance.